Interval-Valued Semiprime Fuzzy Ideals of Semigroups - Sukhendu Kar; Paltu Sarkar; Kostaq Hila (Advances in Fuzzy Systems)
We introduce the notion of (i-v) semiprime (irreducible) fuzzy ideals of semigroups and investigate its different algebraic properties. We study the interrelation among (i-v) prime fuzzy ideals, (i-v) semiprime fuzzy ideals, and (i-v) irreducible fuzzy ideals and characterize regular semigroups by using these (i-v) fuzzy ideals.